A Pragmatic Study of the Impact of a Brief Mindfulness Intervention on Prisoners and Staff in a Category B Prison and Men Subject to Community-Based Probation Supervision - Davies, Jason (International journal of offender therapy and comparative criminology, 2021)
Objectives:This article presents two studies assessing the impact of mindfulness in prison (prisoners and staff) and non-custodial settings.Method:Study 1?prisoners (n?=?17) and staff (n?=?15) in a UK prison completed a mindfulness program; 16 individuals acted as a single time point comparison. Data were collected using self-report, computer based and physiological measurement. Study 2?men under community probation supervision were allocated to mindfulness (completed, n?=?28) or TAU (n?=?27). Data were collected using self-report mindfulness measures.Results:Study 1?statistically significant (increases in mindfulness skills (?2p?=?.234 to ?2p?=?.388), cognitive control (?2p?=?.28), and heart rate variability (SDNN; ?2p?=?.41) along with significant decreases in stress (?2p?=?.398) were found. In study 2, the mindfulness group showed non-significant improvements in mindfulness skills.Conclusion:The findings suggest brief mindfulness interventions could make an important contribution to offender rehabilitation and custodial staff wellbeing.